1954
DOI: 10.1021/j150516a011
|View full text |Cite
|
Sign up to set email alerts
|

Charcoal Sorption Studies. II The Sorption of Water by Hydrogen Treated Charcoals

Abstract: Oxygen has been removed from three types of charcoal by treating them with hydrogen at 1000°. It has been shown that this results in a lowered water sorption at humidities of less than 80% for all three charcoals. The amount of oxygen so removed has been measured for one of these charcoals (coconut shell). Surface areas are substantially unchanged by the removal of oxygen. Oxidation of the surface is shown to increase the sorption of water by charcoal. It is suggested that the data are in accord with the clust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

1958
1958
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Almost all of the benzene is sorbed over a very narrow range of pressure, and for equal amounts of sorption a higher pressure is required with Type A polystyrene than with Type B. This behavior is associated with adsorption in rather narrow sizedistributions of pores (9). In fact, the present heat and isotherm data are best correlated by assuming that porous adsorption occurs.…”
Section: Results Akd Discussionmentioning
confidence: 69%
“…Almost all of the benzene is sorbed over a very narrow range of pressure, and for equal amounts of sorption a higher pressure is required with Type A polystyrene than with Type B. This behavior is associated with adsorption in rather narrow sizedistributions of pores (9). In fact, the present heat and isotherm data are best correlated by assuming that porous adsorption occurs.…”
Section: Results Akd Discussionmentioning
confidence: 69%
“…In the figure, a steep increase in the weight of S1 occurs at relatively low humidity, and this feature indicates that S1 is more susceptible to moisture than the other activated carbons. In the previous reports of the moisture effect on the adsorption ability or capacity of cartridges of respirators [1][2][3][4][5][6][7][8][9][10][11][12][13][14] , there is little description of the porous structures and the specific surface areas of activated carbon contents of the cartridges. However, from the comparison of the curves in Fig.…”
Section: The Effect Of Moisture Contents Of Activated Carbonmentioning
confidence: 99%
“…3 (a)). In the previous reports [1][2][3][4][5][6][7][8][9][10][11][12][13][14] , the relative humidity of the test gas flow was taken as the index of adsorption capacity in relation to the breakthrough time. However, the weight increase by preliminary moisture adsorption relative to the weight before preconditioning is another simple indicator of the adsorption capacity of the carbon bed, and we have used this indicator for the breakthrough time in the figures.…”
Section: The Effect Of Moisture Contents Of Activated Carbonmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these influencing factors, moisture content has been the focus of many quantitative researches, and there are many reports [6][7][8][9][10][11][12][13][14][15][16][17][18][19] regarding its effect on gas filters or experimental packed beds of activated carbon at room temperature (approximately at 293-298 K). Further, Wood et al have reported the effective estimation of the breakthrough time of activated carbon beds for organic vapors 20,21) which covers the effect of all levels of relative humidities by extension of the Wheeler-Jonas breakthrough time equation [22][23][24] modified by Yoon et al 25,26) .…”
Section: Introductionmentioning
confidence: 99%